PROFIL KENAKALAN REMAJA DI TINJAU DARI POLA ASUH ORANG TUA DAN PEKERJAAN ORANG TUA DI KELAS VII SMPN 13 PEKANBARU - Robiyandi Robiyandi; Tri Umari; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Distorted action is a problem that often occurs in adolescents, both in the family environment, school and community environment. In schools it is shown by the act of fighting among students, doing the graffiti of the school wall, often absent. Because there are still a lot of juvenile delinquency occurs, therefore researchers feel the need to research about juvenile delinquency in terms of parental care and parent work. The purpose of this research is to know the description of juvenile delinquency level, to know the description of parent's parenting pattern, to know the description of parent's job, to know the description of juvenile delinquency based on parenting pattern, to know the description of juvenile delinquency level based on the work of the parents. The research method used qualitative method of descriptive approach. Data collection techniques used questionnaires. The population is 400 students with a sample of 200 students. The results showed that the picture of juvenile delinquency rates was higher among parents applying permissive parenting patterns in which the permissive parenting pattern was in very high category. While the picture of a higher level of juvenile delinquency occurs in students whose parents work entrepreneurs are in very high category.Keywords: Juvenile Delinquency, Patterns of Parenting, Parent Occupation